KAJIAN LITERATUR TENTANG FUNGSI MANAJEMEN BAGI KURIKULUM PENDIDIKAN ANAK USIA DINI - Suci Aulia Sari Abu Bakar; Yoyon Suryono; Puji Yanti Fauziah (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Widya Gama Mahakam Samarinda, 2023)
Early childhood education management is an effort to organize the process of early childhood education (PAUD) in order to achieve the goal of helping children grow and develop. The purpose of PAUD or early childhood education is to provide the best education for children so that it helps their growth and development. One of the things that is important in management is the function of management itself. This research is a literature research with procedures: (1) selecting a topic, (2) exploring information from the selected topic, (3) determining the research focus from the results of information exploration, (4) reading sources relevant to the research focus, (5) making and (6) processing research notes, and (7) compiling reports in the form of research articles. Research data was obtained by utilizing secondary data sources such as books, scientific articles, and websites. Data collection used documentation techniques by utilizing the researcher as a literature research with procedures: (1) selecting a topic, (2) exploring information from the selected topic, (3) determining the research focus from the results of information exploration, (4) reading sources relevant to the research focus, (5) making and (6) processing research notes, and (7) compiling reports in the form of research articles. Research data was obtained by utilizing secondary data sources such as books, scientific articles, and websites. Data collection used documentation techniques by utilizing the researcher as a ning, 2) Organizing early childhood education, 3) Early childhood education learning patterns, 4) Early childhood education evaluation system. So the management function has an important role in the development of the PAUD curriculum. Management functions such as planning, organizing, controlling, and evaluating are needed to develop, implement, and evaluate the PAUD curriculum effectively and efficiently. Planning functions to determine the direction and objectives of the PAUD curriculum, organizing functions to manage resources and determine the roles and responsibilities of each party involved, control functions to ensure that the PAUD curriculum is implemented properly according to plan, and evaluation functions to evaluate the effectiveness of the PAUD curriculum and make repairs if necessary.